Shariah principles of Sukuk structure in Islamic capital market / Norlela Kamaluddin ... [et al.] - Kamaluddin, Norlela; Ab. Manan, Siti Khadijah; Sufian, Fadzlan; Nu Nu Htay, Shila (Academy of Contemporary Islamic Studies, 2015)
Malaysia as the pioneer of Sukuk has captured the global Sukuk share market positively and has a successful track record in innovating and commercializing many shariah-compliant products. Nevertheless, the literatures on Sukuk are far than enough particularly its theoretical aspect. This paper explains the definition and importance of Sukuk and the comparison between Sukuk and bond. Furthermore, the shari'ah principles in structuring Sukuk, namely profit sharing principles of Mudarabah and Musharakah; sale based principles of Murabahah, Bay' Bithaman Ajil, Salam and Istisna' and hire purchase principle of Ijarah will be described. This paper indicates that a continuous innovative and creative Sukuk structures are needed in order to protect the sustainability of Islamic financial sources.